2009
DOI: 10.1366/000370209788964467
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reflectance and Transmittance Measurements on Absorbing and Scattering Small Samples Using a Modified Integrating Sphere Setup

Abstract: The aim of the present paper is to analyze reflectance and transmittance measurements on small scattering and absorbing samples. The long term goal is to perform quantitative, spectroscopic in vivo measurements of pigments in small samples of plant material. Small samples such as small leaves constitute a special experimental challenge in cases in which the sample beam has a larger cross-sectional area than the sample. The experimental errors introduced when measuring reflectance and transmittance on small abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…A conventional spectrophotometer equipped with an integrating sphere is often used to measure reflectance or transmittance to assess for a smooth surface, which allows the physical status of a film to be monitored [20,21]. Transmittance measurements on small samples are much more accurate than reflectance measurements [20]. Therefore, the ultraviolet spectroscopy (UV)-Vis (200–800 nm) transmission spectra of different composite films were obtained (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A conventional spectrophotometer equipped with an integrating sphere is often used to measure reflectance or transmittance to assess for a smooth surface, which allows the physical status of a film to be monitored [20,21]. Transmittance measurements on small samples are much more accurate than reflectance measurements [20]. Therefore, the ultraviolet spectroscopy (UV)-Vis (200–800 nm) transmission spectra of different composite films were obtained (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of TNPs or TNTs changed the functional properties of EFCs. First, the MC values of the films were higher than the films without them, which may result from the super-hydrophilicity of TNPs [20]. Second, the solubility in water values of the films were lower than the films without them.…”
Section: Resultsmentioning
confidence: 99%
“…Brunsting et al 30 demonstrated the experimental adaptations that are needed for both the reference and sample optical trains to accurately measure samples of small diameter and yield results with correct ratios. Jernshøj and Hassing 31 studied this problem further and showed that in order to measure small samples using a mask that there are not only light–mask interactions where the beam impinges upon the mask, but also reflections among the sample, the mask, and the port itself. In a similar manner, we have found that there are multiple reflection effects between the protective glass and the sample itself.…”
Section: Introductionmentioning
confidence: 99%
“…Reflection measurements performed on different kind of green plants and on different plant parts are similar and contain almost identical spectral information. The example in figure 1 shows reflection spectra from two types of leaves of a Hibiscus, rosa sinensis, namely a foliage leaf and a sepal Jernshøj & Hassing (2009). The spectra shows differences in the absolute reflection values, but are very similar with respect to spectral information.…”
Section: Introductionmentioning
confidence: 99%
“…carotenes, in the sepals than in the green leaves. A quantitative analysis of chlorophyll and carotenoid from these spectra is possible, when applying empirical models, this reflects the complex scattering and interaction processes taking place in the leaf Jernshøj & Hassing (2009);Kortüm (1969). However, due to the poorly resolved spectra, it may be impossible to discriminate between the presence of closely related molecular species, such as the antioxidants α-and β-carotene.…”
Section: Introductionmentioning
confidence: 99%